(untitled) (Global Journal of Human-Social Science, 2025)
Elections whether through direct or indirect democracy are widely considered an instrument ensuring inclusive political participation in which all citizens are equal regardless of their background The culture of most African societies often hinders participation of the vulnerable and minority groups Raleigh 2010 Somalia s minority clans suffered painful exclusions and servitude David Seaboyer 2011 Democracy in Africa is one of the most unpredictable political phenomena owing to the multiplicity of factors that support or hinder electoral outcomes Ndirangu 2022 Therefore having in mind all those factors this paper explores how the marginalized groups including women minorities and internally displaced persons IDPs were included in politics during Puntland s first-ever democratic local councillor elections held in 36 districts after several years of statebuilding since 1998 shifting from the clan-based model where the ultimate political decisions were made by the traditional clan elders To delve into the key factors like the level of political participation the obstacles and the attitudes of marginalized groups towards their involvement in politics this study mainly relied on a mixed methods approach using both quantitative analysis of voter demographics and election data and key informant interviews with policymakers elected local councilors political associations party representatives electoral officials polling staff officials civil society organizations academicians and members of marginalized groups particularly those who are involved in electoral processes using semi-structured After rigorous analysis the study found that of the 780 elected local councillors only 160 are female changing into 942 local councillors only 163 women four are minorities four represent internally displaced peoples IDPs of the south-central of Somalia and none represent people with special needs or disabled people Such gender disparities and minimal inclusion of the marginalized can be attributed to the lack of a cohesive advocacy strategy in place insufficient funding and inadequate time for campaigning the undeniable influence of political party leaders over poll workers a tremendously higher illiteracy rate and limited law enforcement